The Strategy of a Tourism Office in Facing Refocusing and Budget Reallocation - Saeni, Asrini A.; Pande, Jenica Sampe; Ibrahim, Erni Cahyani; Anwar, Ahsan (KnE Social Sciences, 2022)
The Covid-19 pandemic is not only a health problem but has also affected the economy. Economic growth has contracted so it has been necessary for the Indonesian Government to make program adjustments and reallocate the budget to anticipate further impacts. The tourism sector has been a center of attention of refocusing and reallocation of budgets because it is not a primary focus in dealing with Covid-19. This study sought to reveal the strategy of the Tourism Office of Maros Regency to deal with the refocusing and reallocation set by the Central Government in the context of dealing with the Covid-19 pandemic. The results revealed that budget refocusing and reallocation were carried out as an effort to better cope with Covid-19 by focusing on health, social safety nets, and mitigating economic impacts. For programs that are considered pillars of tourism, the Tourism Office only changed the volume of activities so that tourism activities could continue to run. The Tourism Office tried to remain consistent with the existing tourism planning to achieve the tourism targets that had been previously determined. Tourism planning is also a requirement for the Tourism Office to obtain Special Allocation Funds from the Ministry of Tourism, both physical and non-physical. This is one of the budget sources that has made tourism activities in Maros Regency continue to thrive during the Covid-19 pandemic. Keywords: strategy, tourism office, Covid-19, refocusing, reallocation